The weaponising of COVID-19: Contamination prevention and the use of spit hoods in UK policing. (December 2022) - De Camargo, Camilla
The COVID-19 pandemic has produced a radically changed world for everyone, but its effects on police officers has been particularly acute. Officers have been subject to increased cough and spit attacks as offenders have sought to weaponise the coronavirus, and forces have responded by encouraging officers to use enhanced methods of contamination prevention. The controversial argument of whether using 'spit hoods' is a necessary tool in policing has been resurrected, although evidence of their ineffectiveness in the fight against COVID-19 has been brought to light more recently. Drawing on interview data obtained from 18 police officers in 11 UK forces over the summer of 2020, this article draws on interview narratives discussing contamination prevention, policing the pandemic, and the use of spit hoods.